Go Camping! - Bode, Heather L. (Oxford: Capstone Global Limited, 2023)
"Roasting marshmallows, stargazing, nature hikes, and fishing. Experience the fun and adventure of a camping trip! Learn about the types of camping, the supplies you'll need, and the adventure that awaits you in the wild outdoors"--
Camping by the Numbers -- Camping Categories -- Getting the Goods -- Camping Fun and Games -- Be a Safety Superstar -- The Pitch and Pack Pro -- Glossary -- Read More -- Internet Sites -- About the Author.
Includes bibliographical references.
Ages 8-11 years
Grades 4-6
Keywords: Camping -- Juvenile literature